Relationship analysis among intergeneric hybrids of Ascocentrum based on floral characters (Current Horticulture, 2024)
A study was undertaken for characterizing 30 intergeneric hybrids of Ascocentrum orchid based on floral characters and cluster  analysis. The results showed that variety V25 (Mokara Syam Ascocenda Doung Porn) produced more number of spikes/plant/year  (7.86), whereas, variety V11 (Vascostylis Blue Bay White) produced more number of florets/spike (40.67). Hybrid V3 (Ascocenda Kultana × Vanda Bitzs Heartthrob) had highest length (9.33 cm) and width (9.00 cm) of flower. Cluster analysis with 14 floral  characters was done by classifying hybrids/varieties into 12 groups. Cluster 2 and 5 had five members, whereas, cluster 11 and 12  with only one member each. The cluster 2 and cluster 5 were less similar to each other with an inter-cluster distance 6.27,whereas  highest inter-cluster distance was observed in cluster 6 and cluster 10 (41.47). Cluster 10 had high mean values for spike length (51.12  cm), flower length (7.94 cm) and width of flowers (7.50 cm). whereas cluster 6 which included V6 (Ascocenda Sirichi Fragrance) and  V11 (Vascostylis Blue Bay White) had lowest internodal length with the highest value for number of florets/ spike. This cluster also  observed to have low flower length and width (2.52 cm and 2.42 cm, respectively). This indicated that these varieties produce flowers  in the dense bunch.
Keywords: Floral character; Intergeneric hybrid; Cluster analysis; Ascocentrum; Mokara; Ascocenda; Vascostylis